DEVELOPMENT OF A DICTIONARY OF HOSPITALITY TERMS AS A READING E-BOOK FOR CLASS XI HOSPITALITY ACCOMMODATION STUDENTS IN SMKN 3 BLITAR - Gilang Davis Romansyach; Ahmad Saifudin; Siti Rofi'ah (IKIP Siliwangi, 2023)
The purpose of this research is to develop a dictionary of hospitality terms as an e-book reading. The reason behind the development of this product is that hospitality terms in a foreign language are very important to be learned and understood by students majoring in hospitality accommodation. The lack of students' knowledge about the meaning of hospitality terms and the absence of specific learning media to learn the meaning of hospitality terms, made researchers interested in developing a dictionary of hospitality terms in the form of an e-book to make it easier for students in understand foreign hospitality terms. This development research uses the ADDIE model. Data collection was carried out through a questionnaire. Questionnaires were distributed to 30 class XI students majoring in hospitality accommodation (XI APH 3) at SMKN 3 Kota Blitar. The findings show that students' evaluation of the existence of a dictionary of hospitality terms in the form of an e-book received a positive response. This dictionary of hospitality terms made them more enthusiastic. They would use this dictionary of hospitality terms again to learn the meaning of hospitality terms. This dictionary can be learned and used by students majoring in hospitality accommodation at all levels.Â Keywords:Â Dictionary; Hospitality Terms; Media Development